2020
DOI: 10.1002/prp2.576
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism, reaction phenotyping, enzyme kinetics, CYP inhibition and induction potential of ataluren

Abstract: Ataluren promotes ribosomal readthrough of premature termination codons in mRNA which result from nonsense mutations. In vitro studies were performed to characterize the metabolism and enzyme kinetics of ataluren and its interaction potential with CYP enzymes. Incubation of [14C]‐ataluren with human liver microsomes indicated that the major metabolic pathway for ataluren is via direct glucuronidation and that the drug is not metabolized via cytochrome P450 (CYP). Glucuronidation was also observed in the incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…For comparison of CL int in different tissues, CL int was expressed per gram of tissue by correcting the values for microsomal protein yield, resulting in a scaled CL int. 20 The scaled CL int values of ningetinib in HLMs and HIMs were 36.7 and 4.66 μL·min −1 ·g −1 tissue, respectively, which showed that the liver had a higher metabolic contribution in M1 formation than the intestine.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…For comparison of CL int in different tissues, CL int was expressed per gram of tissue by correcting the values for microsomal protein yield, resulting in a scaled CL int. 20 The scaled CL int values of ningetinib in HLMs and HIMs were 36.7 and 4.66 μL·min −1 ·g −1 tissue, respectively, which showed that the liver had a higher metabolic contribution in M1 formation than the intestine.…”
Section: Resultsmentioning
confidence: 91%
“…V max = 4.30 ± 0.26 pmolÁminÁmg −1 protein, intrinsic clearance CL int = 0.918 μLÁminÁmg −1 protein) than in HIMs (K m = 6.30 ± 1.52 μM, V max = 1.39 ± 0.12 pmolÁmin −1 Ámg −1 protein, CL int = 0.221 μLÁminÁmg −1 protein). For comparison of CL int in different tissues, CL int was expressed per gram of tissue by correcting the values for microsomal protein yield, resulting in a scaled CL int 20. The scaled CL int values of ningetinib in HLMs and HIMs were 36.7 and 4.66 μLÁmin −1 Ág −1 tissue,…”
mentioning
confidence: 99%
“…This defective gene product causes many diseases, including muscular dystrophy, cystic brosis, and some cancers (38-40). Ataluren is a small-molecule nonsense repressor that stimulates stop codon reading and thereby acts as a treatment for these diseases (41). The addition of Stop-POST5 (containing the UGA stop codon at the A-site) is shifted to extension.…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentrations of the free ataluren in human plasma after administration of the most typical dosage regimen (10, 10, 20 mg/kg) is much lower than inhibition constants toward these enzymes due to the high protein binding of the drug. What is more, clinically irrelevant induction of CYP2B6 and CYP2C9 activity in cultured primary human hepatocytes was also observed [ 42 ].…”
Section: Main Body Of Reviewmentioning
confidence: 99%